Reassessing Criminal Responsibility of Mentally Disordered Offenders in Indonesian Homicide Cases: Judicial Interpretation of Article 44 KUHP - Melkianus Ndaumanu; Yanto M.P. Ekon; Ellon Belwan Cornelius Mau (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
This study examines the judicial interpretation of criminal responsibility for mentally disordered offenders in homicide cases under Article 44 of the Indonesian Criminal Code (KUHP). Despite its normative function as a ground for excluding criminal liability, the application of Article 44 remains inconsistent in judicial practice. Using a normative juridical approach combined with case analysis, this research analyzes court decisions across multiple judicial levels and evaluates the extent to which psychiatric evidence influences legal reasoning. The findings indicate that judges tend to rely on behavioral indicators such as functional normality, coherence of testimony, and the presence of rational motives, rather than prioritizing clinical psychiatric assessments. As a result, defendants diagnosed with severe mental disorders, including schizophrenia, may still be deemed criminally responsible. This practice reflects a shift from a capacity-based approach toward a behavior-based interpretation, which risks undermining the doctrinal principle of culpability (schuld). Furthermore, the study highlights the limited evidentiary weight assigned to Visum et Repertum Psychiatricum and the lack of interdisciplinary integration between law and psychiatry. A comparison with Article 39 of the new Indonesian Criminal Code demonstrates a significant paradigm shift toward a more precise, evidence-based, and rehabilitative framework. This research concludes that strengthening judicial understanding of mental health, enhancing the role of expert evidence, and ensuring consistent implementation of the new legal framework are essential to achieving a more just and humane criminal justice system.